The genus Milnesium (Eutardigrada, Apochela, Milnesiidae) in Argentina: description of three new species and key to the species of South America - Rocha, Alejandra M.; González-Reyes, Andrea X.; Ostertag, Belén; Lisi, Oscar (European Journal of Taxonomy, 2022)
A revision of microscope slides deposited between 2014 and 2017 in the collection of Rocha and Doma (National University of La Pampa, Argentina) revealed three new species of the genus Milnesium Doyère, 1840: M. pelufforum sp. nov., M. irenae sp. nov. and M. quiranae sp. nov. Milnesium pelufforum sp. nov. is mostly characterized by ten transverse bands of sculptured cuticle and pseudoplates (the first band, until now, never detected in the genus), six peribuccal lamellae and claw configuration [2-2]-[2-2] in young or [2-3]-[3-2] in senior specimens. Milnesium irenae sp. nov. is mostly characterized by complex cuticular ornamentation including a fine reticulation different from the typical one in the genus; it also has pseudoplates, six peribuccal lamellae, medioventral peribuccal papilla reduced, stylets, their furcae and supports very developed, and claw configuration [2-3]-[2-2]. Milnesium quiranae sp. nov. is mostly characterized by smooth cuticle, six peribuccal lamellae, and claw configuration [3-3]-[3-3]; with growing, the medioventral peribuccal papilla reduces and the buccal tube becomes wider. With the present contribution the genus Milnesium now has 48 valid species, and the number of described limno-terrestrial tardigrade species from South America has risen to 11, including 8 from Argentina with 5 from Salta and La Pampa province.